Mekanisme Produksi Siaran Langsung dan Tidak Langsung (Taping) di Radio dan TV - Effendy, Erwan; Ningsih, Putri Setia; Sinembela, Risky Fahmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research was structured to explain how the mechanism for the production of direct and indirect broadcasts on radio and television. The results of this study The process of broadcasting mechanisms occurs from the moment the idea is created until the idea is disseminated. The steps include the initiator of the idea which in this case is the communicator, then the idea is converted into a form of message that can be sent both verbally and nonverbally through channels and or means of communication that enable the message to reach a wide audience (communicant). live broadcast mechanism can be done in the studio or outside the studio. Broadcasts in the studio, for example, broadcasts of talk shows/programs, dialogues and so on. Indirect broadcasts occur between shooting/coverage and broadcasting, there is a grace period, so there is an opportunity to prepare the program better through the editing process. Keywords: mechanics,broadcasting,production,broadcasting,techniques